The Influence of Organizational Culture and Work Ethics on Lecturer Competence and Performance - L Wairisal, Paulus (Journal of World Science, 2022)
Introduction: Organizational culture determines the direction of individual behavior of an institution. This study aims to analyze and explain the direct influence of organizational culture on competence and the indirect influence of organizational culture on lecturer performance through competence. Analyze and explain the direct effect of work ethic on competence and the indirect effect of work ethic on lecturer performance through competence. Analyze and explain the effect of competency on lecturer performance. Method: This type of research is explanatory research with a survey approach. The sampling technique is a saturated sample with a total of 72 lecturers as respondents. The type and source of data are Primary Data. Result: The hypothesis test results prove that organizational culture has a significant positive indirect effect on lecturer performance through competence (0.031 <0.05). Work ethic significantly positively affects lecturer performance through competence significance (0.019 <0.05). Competence has a significant direct effect on performance (0.003 <0.05). Conclusion: Competence has an intervening role in organizational culture and works ethic on lecturer performance because it has a very high value. If the competency is increased by one interval, the lecturer's performance will increase.